SERVITIZE, DESIGN AND CO-CREATE VALUES THROUGH SOCIAL MEDIA - Ilugbo, Gbenga Adeyemi (My University, 2015)
This study examines from service design perspectives to what extent designers understand the term “Servitization” and who is responsible for value definition. The study also dives into looking the impact and role of customers’ involvement in value definition and values co-creation. Further in the prevalent influence of current social media to what extent has social media impact and influence customers’ involvement for idea generation (Idealization process) in design process. Qualitative research method is applied to compare three case study organizations in service and manufacturing industries for proper persecutions. Results of study indicate that lack of understanding of servitization mainly by service and products designers limits service innovation and leads to customers’ hostility. And design with the market rather for the market can only be achieved without limiting customer involvement. So, in order to reduce customers’ hostility and design with the market, social media creates a platform to reduce information alteration, cycle time, and increase customers’ involvement in design process by co-creating and transferring values definition from customers to designers. However, it also poses some threat if organizations cannot exercise active control. Finally, the study also establishes the difference between design and service design that when organization get proper understanding of, will improve design process significantly.
Keywords: Servitization; Service design; Value definition & co-creation.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|